Narratives and journeys in rock art : a reader - Nash, George,; Mazel, Aron D., (Archaeopress Publishing Ltd, 2018)
Why publish a reader? Today, it is relatively easy and convenient to switch on your computer and download an academic paper. However, as many scholars have experienced, historic references are difficult to access. Moreover, some are now lost and are merely references in later papers. This can be frustrating. This text provides a series of papers from all over the world that extend as far back as the 1970s when rock art research was in its infancy. The papers presented in the reader reflect the development in the various approaches that have influenced advancing scholarly research.